Maternal multiple micronutrient supplementation and other biomedical and socioenvironmental influences on children's cognition at age 9-12 years in Indonesia: follow-up of the SUMMIT randomised trial - Elizabeth L Prado, PhD; Susy K Sebayang, PhD; Mandri Apriatni, MA; Siti R Adawiyah, BS; Nina Hidayati, BS; Ayuniarti Islamiyah, BS; Sudirman Siddiq, BS; Benyamin Harefa, BS; Jarrad Lum, PhD; Katherine J Alcock, DPhil; Michael T Ullman, PhD; Husni Muadz, PhD; et al. (Elsevier, 2017)
Background: Brain and cognitive development during the first 1000 days from conception are affected by multiple biomedical and socioenvironmental determinants including nutrition, health, nurturing, and stimulation. An improved understanding of the long-term influence of these factors is needed to prioritise public health investments to optimise human development. Methods: We did a follow-up study of the Supplementation with Multiple Micronutrients Intervention Trial (SUMMIT), a double-blind, cluster-randomised trial of maternal supplementation with multiple micronutrients (MMN) or iron and folic acid (IFA) in Indonesia. Of 27 356 live infants from birth to 3 months of age in 2001-04, we re-enrolled 19 274 (70%) children at age 9-12 years, and randomly selected 2879 from the 18 230 who were attending school at a known location. Of these, 574 children were oversampled from mothers who were anaemic or malnourished at SUMMIT enrolment. We assessed the effects of MMN and associations of biomedical (ie, maternal and child anthropometry and haemoglobin and preterm birth) and socioenvironmental determinants (ie, parental education, socioeconomic status, home environment, and maternal depression) on general intellectual ability, declarative memory, procedural memory, executive function, academic achievement, fine motor dexterity, and socioemotional health. The SUMMIT trial was registered, number ISRCTN34151616. Findings: Children of mothers given MMN had a mean score of 0·11 SD (95% CI 0·01-0·20, p=0·0319) higher in procedural memory than those given IFA, equivalent to the increase in scores with half a year of schooling. Children of anaemic mothers in the MMN group scored 0·18 SD (0·06-0·31, p=0·0047) higher in general intellectual ability, similar to the increase with 1 year of schooling. Overall, 18 of 21 tests showed a positive coefficient of MMN versus IFA (p=0·0431) with effect sizes from 0·00-0·18 SD. In multiple regression models, socioenvironmental determinants had coefficients of 0·00-0·43 SD and 22 of 35 tests were significant at the 95% CI level, whereas biomedical coefficients were 0·00-0·10 SD and eight of 56 tests were significant, indicating larger and more consistent impact of socioenvironmental factors (p<0·0001). Interpretation: Maternal MMN had long-term benefits for child cognitive development at 9-12 years of age, thereby supporting its role in early childhood development, and policy change toward MMN. The stronger association of socioenvironmental determinants with improved cognition suggests present reproductive, maternal, neonatal, and child health programmes focused on biomedical determinants might not sufficiently enhance child cognition, and that programmes addressing socioenvironmental determinants are essential to achieve thriving populations. Funding: Grand Challenges Canada Saving Brains Program.